2017
DOI: 10.3847/1538-3881/153/3/103
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Historical Flux of Planetary Impactors

Abstract: The impact cratering record of the Moon and the terrestrial planets provides important clues about the formation and evolution of the Solar System. Especially intriguing is the epoch ≃3.8-3.9 Gyr ago (Ga), known as the Late Heavy Bombardment (LHB), when the youngest lunar basins such as Imbrium and Orientale formed. The LHB was suggested to originate from a slowly declining impactor flux or from a late dynamical instability. Here we develop a model for the historical flux of large asteroid impacts and discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
221
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(238 citation statements)
references
References 97 publications
15
221
0
Order By: Relevance
“…In order to evaluate this expression, we have to specify the architecture of the giant planets. In this regard, it is crucial to note that the orbits of the giant planets almost certainly experienced significant divergent migration early in the solar system's lifetime, owing to a transient dynamical instability that ensued due to their interactions with a ∼ 20 M ⊕ primordial disk of planetesimals extending from ∼ 15 AU to Neptune's present-day orbit (Tsiganis et al 2005;Nesvorný & Morbidelli 2012). This means that during the epoch relevant to cluster-induced dynamics, the orbital configuration of the giant planets was likely more tightly packed than today's solar system.…”
Section: Twist Of the Solar Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to evaluate this expression, we have to specify the architecture of the giant planets. In this regard, it is crucial to note that the orbits of the giant planets almost certainly experienced significant divergent migration early in the solar system's lifetime, owing to a transient dynamical instability that ensued due to their interactions with a ∼ 20 M ⊕ primordial disk of planetesimals extending from ∼ 15 AU to Neptune's present-day orbit (Tsiganis et al 2005;Nesvorný & Morbidelli 2012). This means that during the epoch relevant to cluster-induced dynamics, the orbital configuration of the giant planets was likely more tightly packed than today's solar system.…”
Section: Twist Of the Solar Systemmentioning
confidence: 99%
“…This is because the outward ejection of ∼ 20 M ⊕ of planetesimals that occurred during the instability was the last major expulsion of icy material into the trans-Neptunian region, and had this event occurred while the cluster was still present, the Oort cloud would have been rendered unbound by passing stars. Consequently, for the calculation at hand, we adopt a compact multi-resonant configuration for the giant planets where Jupiter and Saturn, as well as Uranus and Neptune are locked into 3:2 mean motion resonances while Saturn and Uranus are entrained into a 4:3 resonance, which has been previously shown to adequately serve as an initial condition for the Nice model instability (although we also note that the specific choice of resonance indexes does not affect our results on a qualitative level; Batygin & Brown 2010;Nesvorný & Morbidelli 2012). The planetesimal disk is modeled as a series of 20 concentric rings, equally spaced between 15 and 35 AU, each containing 1 M ⊕ of material.…”
Section: Twist Of the Solar Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a prior inwards migration of the giant planets can explain Jupiter's composition and the asymmetry of its Trojan populations (Öberg & Wordsworth 2019; Pirani et al 2019). Additionally, the giant planets likely underwent at least one gravitational instability which has re-ordered the planets at some, still-uncertain, previous epoch (Thommes et al 2002;Tsiganis et al 2005;Morbidelli et al 2007;Nesvorný & Morbidelli 2012;Morbidelli et al 2018). These instabilities have also shaped the Kuiper Belt and scattered disc.…”
Section: Planetary System Initial Conditionsmentioning
confidence: 99%
“…For comets from the trans-Neptunian belt (with initial distances in a range of 20-30 AU), Nesvorný et al (2017) found that the probabilities of collisions with Venus, the Earth, Mars, and the Moon are 3.7 × 10 -7 , 5.0 × 10 -7 , 9.1 × 10 -8 , and 2.6 × 10 -8 , respectively. For asteroids with initially large semimajor axes, from 1.6 to 3.3 AU, these probabilities were (1.2-1.5) × 10 -2 , (1.0-1.1) × 10 -2 , (3.6-3.9) × 10 -3 , (4.4-5.3) × 10 -4 , respectively.…”
Section: Delivery Of Water and Volatiles Tomentioning
confidence: 99%